Usage of solar shading devices to improve the thermal comfort in summer in a Romanian PassivHaus. (May 2020) - Udrea, Ioana; Badescu, Viorel
The global trend is to increase the thermal comfort in all kinds of buildings, residential and non-residential. At the same time, minimization of energy consumption and improved building sustainability must be achieved. Only precise calculations can keep the balance between maximizing comfort and minimizing energy consumption. The PassivHaus (PH) is a special type of building with low heating energy consumption that fulfills special requirements defined by the Passivhaus Institut of Darmstadt, Germany. The PassivHaus concept has been successfully implemented in climates other than that of Germany. However, current practice in Southern European countries shows that PHs may exhibit overheating in the hot season, a phenomenon which is not very often encountered in Germany. Shading devices may be considered in these southern countries to improve the thermal comfort in PHs during summer. A model of the AMVIC PH office building located near Bucharest, Romania, has been developed using Simergy and EnergyPlus software. The model was validated and calibrated using measured data during summer. Measurements have been used to estimate the classical thermal comfort indices such as predicted mean vote and predicted percent of dissatisfied. Simulations have been performed to study the effect on thermal comfort of several shading devices, such as exterior blinds, exterior shades, and overhangs. Exterior blinds and exterior shades are generally more efficient than overhangs when the results are discussed with reference to transmitted solar energy flux through the windows.